Effects of Intercropping of Sisal and Three Different Leguminous Plants on Soil Bacterial Diversity - Yanqiong Liang; Shibei Tan; Chunping He; Rui Li; Ying Lu; Helong Chen; Xing Huang; Weihuai Wu; Kexian Yi (Agronomy, 2024)
Intercropping is widely utilised in agricultural production to enhance land use efficiency because of its benefits, such as heightened crop productivity and optimised resource utilisation. We investigated the effects of Pinto peanut/sisal (HST), Stylo/sisal (strT) and Grona styracifolia/sisal (JqT) intercropping systems on soil bacterial communities compared with sisal continuous cropping (CK) by using Illumina MiSeq high-throughput sequencing technology. The intercropping system significantly increased the total nitrogen (TN), soil pH and soil moisture levels and decreased the levels of available phosphorus (AP) and available potassium (AK). Minimal variations were observed in Shannon’s and Simpson’s diversity indices between the monoculture and intercropping systems as well as among different intercropping systems. The most abundant phyla observed within the four groups were Proteobacteria, Acidobacteria, Cyanobacteria and Bacteroidetes. At the phylum level, the relative abundances of Proteobacteria, Acidobacteria, Cyanobacteria and Bacteroidetes were 37.37–54.35%, 10.54–21.21%, 3.46–20.43% and 2.15–5.67%, respectively. Compared with ZCK, StrT, JqT and HST treatments led to higher abundance of Cyanobacteria (from 3.46% to 20.43%, 11.37% and 16.58%, respectively) and Bacteroidetes (from 2.15% to 5.67%, 5.21% and 5.10%, respectively). The results of the linear discriminant analysis of effect sizes demonstrated notable variations in the relative abundance of bacterial taxa among various intercropping systems. The dominant categories of the genus in strT and JqT groups were Blastocatellia and Blastocatellaceae-Subgroup4, while Firmicutes was the dominant category of the genus in the HST group. The structure of bacterial communities did not vary between intercropping and monoculture systems. The findings indicated that the impact of the intercropping system on the bacterial community structure was not contingent on the specific intercropping patterns employed.